Migrants Crisis in the Southeast Europe - Selcuk, Mustafa (Sospol : Jurnal Sosial Politik, 2017)
AbstractThe movement of more than a million immigrants to Europe has challenged European policies on the issue and shacked the very foundations of the European Union. Immigrants are not a new phenomenon in Europe especially in the Balkans (South East Europe) examined. The immigrant crisis that erupted in 2015 and 2016 was unique in terms of the number of people, the conditions and the emergencies created. Increased terrorism in Europe and huge number of immigrant arrived Europe via South East Europe, and initiation of immigrant campaigns in Europe on social media helping to immigrants for arrive to central Europe the same time states actor responses towards immigrants crisis. The purpose of this research figure out responses states actors in South East Europe towards immigrant crisis and European Union deal with Turkey. The concept of the research is understanding impact of immigrant crisis between 2015-2016 years, when one of huge number of immigrants arrived Europe and responses states actors South East Europe. The research technique mainly relies on sources such as journal articles, newspaper articles, on-line sources, and research center reports which are related with the immigrant crisis in South East Europe (Balkans) and Turkey. EU and Turkey deal jammed up because of political issues between EU and South East European countries overburdened towards immigrant crisis. While increased immigrant deaths in Aegean Sea positive view regarding to immigrants, even though increased terrorist incidents in Europe started negative view to immigrants.Keywords: Greece, Immigrant Crisis, Refugee, Southeast Europe, Turkey AbstrakPergerakan lebih dari satu juta imigran ke Eropa telah menantang kebijakan Eropa mengenai isu imigran dan menggoyahkan landasan Uni Eropa yang telah mapan selama ini. Imigran bukan fenomena baru di Eropa terutama di Balkan (South East Europe). Krisis imigran yang meletus pada tahun 2015 dan 2016 sangat menarik pada aspek jumlah orang, kondisi dan keadaan darurat yang diciptakan. Meningkatnya terorisme di Eropa dan sejumlah besar imigran tiba di Eropa melalui Eropa Tenggara. Inisiasi kampanye imigran di Eropa melalui media sosial, membantu imigran untuk sampai ke Eropa Tengah pada saat yang sama menimbulkan krisis pada negara. Tujuan penelitian ini adalah untuk mengetahui tanggapan para aktor di Eropa Tenggara terhadap krisis imigran dan kesepakatan Uni Eropa dengan Turki. Konsep penelitian ini adalah pemahaman dampak krisis imigran antara tahun 2015-2016, ketika salah satu dari sejumlah besar imigran Eropa tiba, dan tanggapan negara aktor Eropa Tenggara. Teknik penelitian ini terutama mengandalkan sumber seperti artikel jurnal, artikel surat kabar, sumber daring, dan laporan pusat penelitian yang terkait dengan krisis imigran di Eropa Tenggara (Balkan) dan Turki. Kesepakatan Uni Eropa dan Turki macet karena adanya isu politik antara negara-negara Uni Eropa dan Eropa Tenggara yang terbebani krisis imigran. Sementara, insiden kematian imigran di Laut Aegea meningkatkan pandangan positif mengenai masalah  imigran, meskipun  meningkatnya  insiden  teroris  di  Eropa  mulai  menunjukkan pandangan negatif kepada masalah imigran.Kata kunci: Eropa Tenggara, Krisis Imigran, Pengungsi, Turki, Yunani